Garlic Powder Evaluation as Feed Additive on Nile Tilapia (Oreochromis niloticus L.) Growth Performance, Feed Utilization, Gill Parasitic Treatment, and Monogenean Diversity - Socorro Marisa Salgado-Moreno; Ranferi Gutiérrez-Leyva; Carlos Alfredo Carmona-Gasca; Sergio Martínez-González; José Carmen Ramírez-Ramírez; Carlos Omar De La Cruz-Moreno; Juan José Fernando Borrayo-González (Fishes)
The present study evaluates garlic powder (GP) effects on growth performance, feed utilization, gill parasitic treatment, and monogenean diversity. Thus, a trial was performed under controlled conditions with 84 juvenile Nile tilapia, Oreochromis niloticus (39.8 ± 8.8 g initial weight), from culture ponds with monogenean parasite presence for 30 days. Four balanced diets in protein (32.5%) and lipids (6.4%) with GP inclusion levels of 0%, 1%, 2%, and 3% were formulated, manufactured, and supplied daily at approximately 6.5% body weight/tank. The GP diets, compared to the Control (without GP), indicated that the three inclusion levels did not affect the water quality, survival, growth performance, and feed utilization parameters (p > 0.05). No differences were observed in the parasitological index of prevalence (20–25%), mean intensity (9.6–28), and mean abundance (2.7–5.3) among the experimental diets (p > 0.05), evidencing no effect by inclusion level. Efficacy among GP diets indicated a potential decrease in parasite number (13.4–45.6%) but not all monogenean gill parasites. In conclusion, GP diets did not affect the Nile tilapia survival, growth performance, and feed utilization parameters; therefore, its use is suggested as a preventive alternative for monogenean gill parasites.